Gynecologic Cancer InterGroup (GCIG) Consensus Review for Ovarian Small Cell Cancers. (1st November 2014) - Reed, Nicholas Simon; Pautier, Patricia; Åvall-Lundqvist, Elizabeth; Choi, Chel-Hun; du Bois, Andreas; Friedlander, Michael; Fyles, Anthony; Kichenadasse, Ganessan; Provencher, Diane M.; Ray-Coquard, Isabelle
Abstract : Abstract: Small cell carcinomas of the ovary are uncommon and account for less than 1% of ovarian cancers. They were first recognized in 1979, and a number of reports appeared during the next 2 decades. They are highly aggressive tumors and usually carry a poor prognosis, although this may reflect that most are diagnosed at advanced stage; however, those diagnosed as stage 1A have only 30% to 40% of long-term survivors. More reports followed extending our experience in the diagnosis and management of these rare cancers. The classification is described below and shown in Table 1, but a revision is expected to be published from the World Health Organization in 2014.